2022
DOI: 10.3390/v14061128
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pegylated Interferon for the Treatment of Chronic Viral Hepatitis

Abstract: Ropeginterferon alfa-2b is a novel mono-pegylated and extra-long-acting interferon, being developed for the treatment of myeloproliferative neoplasm (MPN) and chronic viral hepatitis. It has a favorable pharmacokinetic profile and less frequent dosing schedule, i.e., once every two to four weeks, compared to conventional pegylated interferon products, which have multiple isomers and are administered weekly. It was approved for the long-term treatment of polycythemia vera, an MPN, and has been included in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…It has anti-HBV and immunomodulatory effects, and plays a variety of key roles in innate and adaptive immune responses ( 52 ). Many studies have proved that the therapeutic effect of PegIFNα for its induction of the repression of specific interferon-stimulated genes (ISGs) and secretion of antiviral proteins ( 53 , 54 ).…”
Section: Anti-viral Therapy and Host Immune Responsementioning
confidence: 99%
“…It has anti-HBV and immunomodulatory effects, and plays a variety of key roles in innate and adaptive immune responses ( 52 ). Many studies have proved that the therapeutic effect of PegIFNα for its induction of the repression of specific interferon-stimulated genes (ISGs) and secretion of antiviral proteins ( 53 , 54 ).…”
Section: Anti-viral Therapy and Host Immune Responsementioning
confidence: 99%
“…In addition, side effects, including flu-like symptoms, injection site reactions and psychiatric disorders such as depression, have the ability to limit their long-term use. 21 The frequent dosing schedule could make patients less compliant with medications.…”
Section: Introductionmentioning
confidence: 99%
“…IFN‐α therapies have often been associated with a short half‐life, requiring frequent injections ranging from three times each week to once every week. In addition, side effects, including flu‐like symptoms, injection site reactions and psychiatric disorders such as depression, have the ability to limit their long‐term use 21 . The frequent dosing schedule could make patients less compliant with medications.…”
Section: Introductionmentioning
confidence: 99%
“…It can be injected less frequently, for example, once every two weeks [ 16 , 17 , 18 ]. It has been approved for the treatment of polycythemia vera (PV), a myeloproliferative neoplasm (MPN), in the United States and Europe [ 19 , 20 ] and is currently under development for more approvals [ 21 , 22 , 23 , 24 , 25 ]. In its Phase II clinical trial, the application of 450 μg of ropeginterferon alfa-2b every two weeks demonstrated good tolerability and manifested anti-hepatitis B virus (HBV) effects [ 26 ].…”
Section: Introductionmentioning
confidence: 99%